Identification of virus-specific B-cell epitopes by convalescent plasma from COVID-19 patients. (December 2022) - Wang, Ling; Zhao, Juan; Schank, Madison; Khanal, Sushant; Dang, Xindi; Cao, Dechao; Nguyen, Lam N.T.; Zhang, Yi; Wu, Xiao Y.; Adkins, James L.; Brueggeman, Justin; Zhang, Jinyu; et al.
Abstract: Identification of immunologic epitopes against SARS-CoV-2 is crucial for the discovery of diagnostic, therapeutic, and preventive targets. In this study, we used a pan-coronavirus peptide microarray to screen for potential B-cell epitopes and validated the results with peptide-based ELISA. Specifically, we identified three linear B-cell epitopes on the SARS-CoV-2 proteome, which were recognized by convalescent plasma from COVID-19 patients. Interestingly, two epitopes (S 809–823 and R1ab 909–923) strongly reacted to convalescent plasma collected at the early phase (< 90 days) of COVID-19 symptom onset, whereas one epitope (M 5–19) reacted to convalescent plasma collected > 90 days after COVID-19 symptom onset. Neutralization assays using antibody depletion with the identified spike (S) peptides revealed that three S epitopes (S 557–571, S 789–803, and S 809–823) elicited neutralizing antibodies in COVID-19 patients. However, the levels of virus-specific antibody targeting S 789–803 only positively correlated with the neutralizing rates at the early phase (<60 days) after disease onset, and the antibody titers diminished quickly with no correlation to the neutralizing activity beyond two months after recovery from COVID-19. Importantly, stimulation of peripheral blood mononuclear cells from COVID-19-recovered patients with these SARS-CoV-2 S peptides resulted in poor virus-specific B cell activation, proliferation, differentiation into memory B cells, and production of immunoglobulin G (IgG) antibodies, despite the B-cells being functionally competent as demonstrated by their response to non-specific stimulation. Taken together, these findings indicate that these newly identified SARS-CoV-2-specific B-cell epitopes can elicit neutralizing antibodies, with titers and/or neutralizing activities declining significantly within 2–3 months in the convalescent plasma of COVID-19 patients. Highlights: SARS-CoV-2-specific B cell epitopes are identified using COVID-19 convalescent plasma The identified B-cell epitopes can elicit neutralizing antibodies, with titers declining significantly within 2–3 months. The COVID-19 vaccine boosters may be necessary to sustain immunity in recovered patients and vaccinated individuals